Literature Review Uji Evaluasi Sediaan Krim - Neneng Sri Purwaningsih; Siti Novy Romlah; Ayu Choirunnisa (STIKes Kharisma Persada, 2020)
The format of preparation cosmetic in a cream form is still popular in Indonesia, especially for the women. Because its easier to applied, and more comfortable. Literature review of evaluation cream preparation test is to compare the results of cream evaluation preparation from the previous researches, in order to get the best test results and accordance with specified conditions. The general purpose of this research is to know the results of Literature review of evaluation cream preparation test from several journals. Method This research is qualitative research which is Library research Cream evaluation preparation is a Parameters that have been established to determine the stability of cream preparation including organoleptic test, pH test, homogeneity test, type cream test, viscosity test, and scattering test. From the result of organoleptic test, pH test, viscosity test and scattering test review have the results partial test standards, and some doesn’t. this is due to the temperature factor, excessive extract concentration and chemical reaction at the time of storage is accelerated. Whereas at the results of homogeneity test have a quite good homogeneity, and in a type cream test has A/M and M/A type cream.